2021
DOI: 10.3390/ijerph182312743
|View full text |Cite
|
Sign up to set email alerts
|

Come for Information, Stay for Support: Harnessing the Power of Online Health Communities for Social Connectedness during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic created a globally shared stressor that saw a rise in the emphasis on mental and emotional wellbeing. However, historically, these topics were not openly discussed, leaving those struggling without professional support. One powerful tool to bridge the gap and facilitate connectedness during times of isolation is online health communities (OHCs). This study surveyed Health Union OHC members during the pandemic to determine the degree of COVID-19 concern, social isolation, and mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
(36 reference statements)
1
9
0
Order By: Relevance
“…Our study supports that of Patel et al [ 60 ] and Zhang et al [ 9 ], who noted that forums were used the most at the beginning of the first lockdown. It also supports the finding by Green et al [ 43 ] that interest in COVID-19 had decreased substantially by later lockdowns. There was less discussion about it by RDwBC users, and there were no threads specifically for COVID-19 in the CMT forum.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our study supports that of Patel et al [ 60 ] and Zhang et al [ 9 ], who noted that forums were used the most at the beginning of the first lockdown. It also supports the finding by Green et al [ 43 ] that interest in COVID-19 had decreased substantially by later lockdowns. There was less discussion about it by RDwBC users, and there were no threads specifically for COVID-19 in the CMT forum.…”
Section: Discussionsupporting
confidence: 89%
“…A US survey of 28 OHFs for people with chronic illnesses over 13 months found that they were used more during peak lockdown times and the desire for emotional or mental health support increased over time. When moderated well, OHFs can “provide a powerful, intermediate and safe space where conversations about mental and emotional wellbeing can be normalized” [ 43 ]. However, potential negative effects include the distress of hearing about others’ negative experiences regarding COVID-19 [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this prior research did not explore the emotional impacts of a cancer diagnosis, such as fear, depression, anxiety, and suicidal ideation, as identified by Paulson et al [9]. Patients may feel less constrained when communicating online than in a focus group because they can remain anonymous during their interactions with others in virtual discussion groups or boards [10], and discussions about the emotional health impacts of a major diagnosis can be normalized [4].…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Importantly, participation in online health communities extends beyond patients with health conditions to include dedicated caregivers and concerned family members and friends. Within these online health communities, participants engage in behaviors such as (1) information seeking and learning, (2) information sharing and disclosure, and (3) community building [ 12 , 16 , 19 , 22 ]. On balance, research conducted across a range of disciplinary contexts has suggested that online health communities provide a plethora of benefits to participants, including actionable health information and improved mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%